METHODOLOGICAL SPECIFICS OF TEACHING DIALOGUE SPEECH IN FOREIGN LANGUAGE - Buranova Lola Uktamovna (Western European Studies, 2024)
The article presents methodological discussion and recommendations which should be taken into consideration in the process of teaching dialogue speech. Effective communication skills are paramount in language acquisition, and dialogue speech serves as a fundamental aspect of real-life interactions. Drawing upon current research and pedagogical practices, this study examines various methodologies employed to enhance students' proficiency in dialogue speech. There are some specific features which differentiate types of dialogue and replicas in them as well as some methodological specifics of dialogic form of communication have been analyzed
Keywords: dialogue speech; dialogic unity; replica